Determinants Analysis of Turnaround: Empirical Study on Manufacturing Company Registered in Indonesia Stock Exchange - Suratno Suratno; Roza Fitriawati; Syahril Djadang (ETIKONOMI, 2017)
This study examines the corporate turnaround which occurred in the company experiencing financial distress listing on the stock exchanges of Indonesia from 2010 to 2015. The purpose of this study is to prove the influence of company size, free assets, expenses retrenchment to corporarte turnaround. Company size, free assets, and expenses retrenchment moderated by CEO turnover. While Company Size, free assets and expenses retrenchment moderated by independent audit committee. The sample used in this study is 21 companies after going through the sampling process purposive sampling. The research method in this research is using logistic regression and moderated regreression analisys (MRA). The result shows the size of the company and free assets significant positive effect on the turnaround. Expenses retrenchment does not affect the turnaround process. CEO Turnover does not have a significant influence on the process of turnaround. Independent Audit Committee only affect or reinforce the results for the size of the company and free asset in conducting corporate turnaround, while at the expense retrenchment does not have a significant influence.DOI: 10.15408/etk.v16i1.4796